Teen movies: American youth on screen - Shary, Timothy (Short cuts, 2005)
Teen Movies: American Youth on Screen is a detailed look at the depiction of teens on film and its impact throughout film's history. Timothy Shary looks at the development of the teen movie ? the rebellion, the romance, the sex and the horror ? up to contemporary portrayals of ever-changing youth. Films studied include Rebel Without a Cause (1955), Splendor in the Grass (1961), Carrie (1976), The Breakfast Club (1985), and American Pie (1999)
https://katalog.adlr.link/Record/0-769432964